2015
DOI: 10.1039/c5ra05291b
|View full text |Cite
|
Sign up to set email alerts
|

Improving the fuel properties of biodiesel via complementary blending with diesel from direct coal liquefaction

Abstract: Complementary blending of biodiesel from waste cooking oil (BWCO) with diesel from direct coal liquefaction (DDCL) was evaluated to improve the fuel properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(50 reference statements)
2
9
0
Order By: Relevance
“…The CP, CFPP and PP of DDCL reached -41 degC, -49 degC and -62 degC, respectively [15]. These results are well consistent with the results of previous reports [19,20]. Similarly, the melting point of ethanol (ET) and 1-butanol (BT) had lower values of -114 degC and -89 degC, respectively.…”
Section: Compositions and Fuel Properties Of Bwco Ddcl Et And Btsupporting
confidence: 91%
See 2 more Smart Citations
“…The CP, CFPP and PP of DDCL reached -41 degC, -49 degC and -62 degC, respectively [15]. These results are well consistent with the results of previous reports [19,20]. Similarly, the melting point of ethanol (ET) and 1-butanol (BT) had lower values of -114 degC and -89 degC, respectively.…”
Section: Compositions and Fuel Properties Of Bwco Ddcl Et And Btsupporting
confidence: 91%
“…CP, CFPP, and PP are used to characterize the low-temperature flow properties of biodiesel fuels [19]. CP refers to the highest temperature where the cloudy crystals appeared in the sample fuel.…”
Section: Fuel Properties Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an eco‐friendly liquid fuel because it is biodegradable and less harmful to the environment (Altaie et al, 2015; Chiu et al, 2004; Moser and Vaughn, 2010; Vedharaj et al, 2014). The use of biodiesel from waste cooking oil (BWCO) as engine fuel can reduce the consumption of petroleum‐based diesel, thereby reducing waste oil emissions and improving the environment (Cao et al, 2014b; Wang et al, 2015; Xue et al, 2016a). However, the poor cold flow properties lead to the quickly gel or solidification of biodiesel in the fuel tanks at low temperature, which eventually affect the use of biodiesel fuels in the diesel engine (Feng et al, 2014; Moser, 2014b; Xue et al, 2016b; Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Vigorously developing of biodiesel has great strategic significance for solving the shortage of petroleum resources, reducing environmental pollution and the greenhouse effect, and ensuring national energy safety [10]. As an alternative fuel for petrochemical diesel, biodiesel has attracted wide attention from all over the world, and large-scale production has been formed in European and American countries [11]. The economic feasibility analysis of biodiesel [12,13], the selection of raw materials, the optimization of production process, and the research of biodiesel combustion emissions have been reported at home and abroad [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%